Effect of a Transverse Magnetic Field on Buoyancy-Driven Flow and Heat Transfer in a Porous Trapezoidal Enclosure - Habibis Saleh; Ishak Hashim (Indonesian Journal of Physics, 2011)
The effect of a magnetic field on buoyancy-driven flow and heat transfer in a trapezoidal enclosure filled with a fluid-saturated porous medium is studied numerically using the finite difference method. The inclined sloping boundaries are treated by adopting staircase-like zigzag lines. The sloping walls are maintained isothermally at different temperatures. The top and bottom horizontal straight walls are kept adiabatic. The results indicate that the heat is transferred almost entirely by pure conduction with a sufficiently large magnetic field. Utilitizing the square geometry is more effective to suppress the heat transfer rate than the trapezoidal geometry.